Surgical management of soft tissue tumors of the abdominal wall: A retrospective study in a high‐volume sarcoma center. Issue 4 (13th June 2021) - Neuberg, Maud; Mir, Olivier; Levy, Antonin; Sourrouille, Isabelle; Dumont, Sarah; Haddag‐Miliani, Leila; Ngo, Carine; Mihoubi, Fadila; Rimareix, Françoise; Le Péchoux, Cécile; Adam, Julien; Honart, Jean‐François; et al.
Abstract: Background: The aim of the study is to evaluate functional and oncological outcomes of patients undergoing abdominal wall soft tissue tumors (AWSTT) surgery. Methods: All consecutive patients that underwent surgery for malignant and intermediate AWSTT from 1999 to 2019 were retrospectively analyzed. Results: Ninety‐two patients were identified, 20 (22%) operated on for a desmoid tumor and 72 (78%) for a soft tissue sarcoma (STS). Fifty‐two patients (57%) had in toto resection of the abdominal wall (from the skin to the peritoneum) and 9 (10%) required simultaneous visceral resection. The closure was direct in 28 patients (30%) and requiring a mesh, a flap or a combination of the two in respectively 42, 16, and 6 patients (47%, 17%, 6%). The postoperative complications rate was 26%. Thirteen patients (14%) developed an incisional hernia after a median delay of 27 months. After a median follow‐up of 40 months, out of the 72 patients operated on for STS, 7 (10%) developed local recurrence and 11 (15%) distant recurrence. The median recurrence‐free and overall survivals were 61 and 116, months respectively. Conclusions: Management of AWSTT requires extensive surgery but allows good local control with an acceptable rate of incisional hernia.